'Education? It is irrelevant to my job now. It makes me very depressed ...': exploring the health impacts of under/unemployment among highly skilled recent immigrants in Canada. - Dean JA; Wilson K (Ethnicity & Health, 2009)
Immigrants account for 20% of the population and 60% of total population growth in Canada (Statistics Canada 2001). The majority of immigrants are accepted for entry to Canada under the Skilled Worker Program in order to fill employment shortages in the labour market (CIC 2007). Recent research has revealed that an increasing number of immigrants who gain entry under this programme face significant barriers to employment. As a result, many remain unemployed or accept employment outside of and below their field of education and training. However, the impacts such employment circumstances have on the health of immigrants have not yet been examined. This paper presents the results of a collaborative research project that explores the health impacts of under/unemployment among skilled immigrants in Mississauga, Ontario, Canada. In-depth interviews are used to examine the experiences of employment and perceptions of subsequent health impacts among 22 recent immigrants. The participants most frequently identified mental health impacts due to a lack of income, loss of employment-related skills, loss of social status and family pressures. These health concerns are also extended to family members. In addition to mental health, physical health is perceived to be affected by employment circumstances through high levels of stress and strenuous working conditions. These findings shed light on the nature of the links between employment and health relationship as well as determinants of immigrant health. Additional research is required to examine the long-term effects of under/unemployment.